Analysis of patients' access to reimbursed biotechnological medicines for multiple sclerosis in Bulgaria and Greece. (17th February 2022) - Seitaridou, Yoana; Tsekov, Ivo; Kamusheva, Maria; Dimitrova, Maria; Petrova, Guenka
ABSTRACT: Objective: The goal is to perform a comparative analysis of multiple sclerosis patients' access to medicines in Bulgaria and Greece. Materials and methods: A comparative analysis of pharmaceutical legislation of Bulgaria and Greece focusing on medicines for multiple sclerosis (MS) was performed. Patients' access to therapy is assessed through the guideline compliance index (GCI) and availability index. Results: The procedures for marketing authorization, pricing and reimbursement, and inclusion of medicines in the positive drug list (PDL) are identical in both European Union member states. Almost all MS medicines authorized for sale in the European Union are included in the Bulgarian and Greek PDL. In both PDLs are included medicines from different groups: immunostimulants, other immunostimulants, immunosuppressors, selective immunosuppressors, and other immunosuppressors. All medicines are fully paid by the health insurance funds in both countries. The average time for inclusion of medicines for MS in the PDL of Bulgaria after their marketing authorization is 3 years. The analysis of pharmacotherapeutic guidelines showed high GCI as it is higher for Bulgaria: 0.846 vs. 0.769 out of 1. Conclusion: The existing legislative measures at the national level of Bulgaria and Greece ensure adequate and timely access of patients with MS to treatment.